Photonic skin for pressure and strain sensing - Kalli, Kyriacos; Chen, Xianfeng; Webb, David J.; Zhang, C.; Van Hoe, Bram; Steenberge, Van G.; Peng, Gangding (My University, 2010)
In this paper, we report on the strain and pressure testing of highly flexible skins embedded with Bragg grating sensors recorded in either silica or polymer optical fibre. The photonic skins, with a size of 10cm x 10cm and thickness of 1mm, were fabricated by embedding the polymer fibre or silica fibre containing Bragg gratings in Sylgard 184 from Dow Corning. Pressure sensing was studied using a cylindrical metal post placed on an array of points across the skin. The polymer fibre grating exhibits approximately 10 times the pressure sensitivity of the silica fibre and responds to the post even when it is placed a few centimetres away from the sensing fibre. Although the intrinsic strain sensitivities of gratings in the two fibre types are very similar, when embedded in the skin the polymer grating displayed a strain sensitivity approximately 45 times greater than the silica device, which also suffered from considerable hysteresis. The polymer grating displayed a near linear response over wavelength shifts of 9nm for 1% strain. The difference in behaviour we attribute to the much greater Young's modulus of the silica fibre (70 GPa) compared to the polymer fibre (3 GPa).
Keywords: Fiber optics; Nanofibers; Optical fibers; Polymers; Silica; Fibers